A novel two-degree-of-freedom MEMS electromagnetic vibration energy harvester. (11th February 2016) - Tao, Kai; Wu, Jin; Tang, Lihua; Xia, Xin; Lye, Sun Woh; Miao, Jianmin; Hu, Xiao
Abstract: In this paper, a vibration-based MEMS electromagnetic energy harvester (EM-EH) device with two-degree-of-freedom (2DOF) configuration has been presented, modeled and characterized. The proposed 2DOF system comprises a primary subsystem for power generation, and an accessory subsystem for frequency tuning. A lumped parametric 2DOF model is built and examined in respect of energy harvesting capabilities. By controlling the mass ratio and frequency ratio, the first two resonances of primary mass can be tuned close to each other while maintaining comparable magnitudes. The 2DOF configuration is expected to be more adaptive and efficient than the conventional 1DOF structure, which could only operate near its sole resonance. The 2DOF EM-EH chip is fabricated on silicon-on-insulator (SOI) wafer through double-sided deep reactive-ion etching (DRIE). Induction coil is only patterned on the primary mass for energy conversion. With current prototype at an acceleration of 0.12 g, two resonances of 326 and 391 Hz with output voltages of 3.6 and 6.5 mV are obtained respectively, providing good validation for the modeling results. This paper offers new insights of implementing a multimodal MEMS EM-EH device.